Analisis Efisiensi Pemasaran Bawang Merah di Desa Kayu Manis Kecamatan Sindang Kelingi Kabupaten Rejang Lebong - Tri Iswahyudi; Gracia Gabrienda; Dwita Prisdinawati (Politeknik Kampar, 2024)
The research entitled Analysis of Marketing Efficiency of Shallots in Kayu Manis Village, Sindang Kelingi District, Rejang Lebong Regency, aims to determine the marketing channels and marketing efficiency of shallots in Kayu Manis Village, Sindang Kelingi District, Rejang Lebong Regency. The research was conducted in June-July 2023. The method for determining shallot farmer respondents was carried out using the purposive sampling method, while for marketing institutions the snowball sampling method was used. The data analysis method itself uses quantitative descriptive by finding out marketing channels and calculating margins. Share margins, marketing profits and marketing efficiency values. The results of this research show that there are two marketing channels, namely: (I) Farmers-collectors-retailers-consumers. (II) Farmers-Consumers. In channel (I) the marketing margin is IDR 11,000,- while the margin share received by farmers is 68.5%. The profit received by collecting traders is IDR 3,237/Kg and retail traders IDR 4,715/Kg, and the marketing efficiency value is 8.7%. . In channel (II) the marketing margin is IDR 0,- while the margin share received by farmers is 100%. The profit received by farmers who are also traders is IDR 27,800/Kg, and the marketing efficiency value is 0.71%.